Clinical considerations on nutrition and lifestyle in old people with osteoporosis and sarcopenia by the CReI-Food study group of the Italian College of Rheumatologists - Laurenti, Rosita; Fioretti, Martina; Martin, Luis Severino; Tanzini, Francesca; Marotto, Daniela; Gubinelli, Emanuela; Migliore, Alberto (Journal of Pharmacy and Nutrition Sciences, 2023)
Osteoporosis is considered the most frequent rheumatic pathology in the elderly population. It is often accompanied by sarcopenia, defined as the progressive loss of skeletal muscle mass and strength. Together, these conditions increase the risk of falls, fractures, disability, lower quality of life, and frequent hospitalization. This means increased healthcare costs for all European countries, due to the increase in the average age and elderly population. Multiple pharmacological therapies are available for osteoporosis, but the prevention seems to be an important tool to reduce the risk of fracture and hospitalization of patients. A healthy lifestyle, consisting of the right amount of nutrients and micronutrients and physical exercise can help prevent the development of osteoporosis and sarcopenia in the elderly. This review brings together the information present in the literature on the benefits that nutrients and micronutrients, naturally present in foods, have on the prevention of these pathologies. it is suggested that a correct intake of proteins, calcium, phosphorus, magnesium, vitamin.D, vitamin C and antioxidants, vitamin K and omega 3, associated with constant physical exercise, can help to contain osteoporosis. It also indicates the right physical exercise for older osteoporotic adults. This document drawn up by the CReI-Food study group of the Italian College of Rheumatologists aims to provide, based on the most recent scientific evidence, indications on correct nutrition and lifestyle for the prevention and treatment of osteoporosis in older people.